Fostering online social capital during the COVID-19 pandemic and new normal - Nugroho, Iwan (Journal of Socioeconomics and Development, 2020)
The impact of the COVID-19 pandemic in Indonesia shows a worrying phenomenon. The trend of increasing cases continues, with the number of confirmed cases approaching 4000 cases a day. Efforts to implement social distancing have been carried out in various regions which show a significant number of cases. At present, the Indonesian government has also prepared economic recovery through the new normal concept, by reopening public service activities and business economy while strictly implementing health protocols. This paper tries to provide a conception of online social capital to recommend solving the pandemic problem. Online social capital will generate productivity in people's lives in adherence to health protocols such as handwashing, wearing face masks, and other protective measures attempts. Furthermore, online social capital is expected to have an impact on smoothing the infection curve and stopping the transmission of the virus. This article suggests four steps including managing infodemic and literacy capacity, staying at home and protecting families from the spread of the virus, utilizing digital communication effectively, and preparing emergency response procedures for disaster management. JEL ClassificationÂ H51; I18; O35